Saddleback Caterpillar Acharia stimulea (Clemens) (Insecta: Lepidoptera: Limacodidae) - Christopher S. Bibbs; J. Howard Frank (EDIS)
Acharia stimulea is best known as a medically significant species. Its spines are strong, acutely pointed, and hollow. They embed deeply into tissue and break off and can interrupt healing as the protoplasm from the venom glands dries into the tissue area. The venom itself can cause a systemic condition called erucism or acute urticaria, for which severe symptoms may include migraines, gastrointestinal symptoms, asthma complications, anaphylactic shock, rupturing of erythrocytes, and hemorrhaging. This 9-page fact sheet was written by Christopher S. Bibbs and J. Howard Frank, and published by the UF Department of Entomology and Nematology, March 2012.